2020
DOI: 10.1016/j.neuint.2020.104729
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory cell cultures to investigate health effects of air pollution exposure: Implications for neurodegeneration

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 102 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…It is well-described that pulmonary, cardiac, renal, vascular endothelial, brain, and small intestine cells express ACE2 receptors and are potential targets for SARS-CoV-2 [ 8 , 9 ]. Another possible mechanism of SARS-CoV-2 brain involvement could be direct spreading across the cribriform plate of the ethmoidal sinus [ 10 , 11 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-described that pulmonary, cardiac, renal, vascular endothelial, brain, and small intestine cells express ACE2 receptors and are potential targets for SARS-CoV-2 [ 8 , 9 ]. Another possible mechanism of SARS-CoV-2 brain involvement could be direct spreading across the cribriform plate of the ethmoidal sinus [ 10 , 11 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Main outdoor air pollutants include carbon monoxide, sulfur dioxide, ozone, nitrogen dioxide, and lead 14 . The polluted air in the city also contains ultra ne particles in high concentrations, and their effect on human health is not fully known 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we report for the first time, an extensive transcriptome profiling of AD ONS cells. Our RNA-Seq results identified altered genes associated with cognitive changes, and a preponderance of highly altered DEGs reported to respond to air pollution, a known environmental risk for AD [ 10 ]. Pathway analyses revealed that DEGs associated with aging, intellectual deficit, and alternative splicing were strongly affected both in AD and MCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory system consists of the olfactory mucosa (OM), located in the upper region of the nasal cavity, where the most superficial layer (olfactory epithelium, OE) is in contact with the external environment. The OE is continuously exposed to potentially harmful agents, including allergens and air pollution, which may contribute to accumulating damage and epigenetic changes to olfactory DNA, potentially with the ability to modify the risk for AD occurrence [ 10 , 11 ]. The OE contains stem cells, including horizontal and globose basal cells which can be readily accessed by routine biopsy, and grown in vitro to form olfactory neurospheres and human neurosphere-derived (ONS) cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%